Mother’s experience in providing complementary food to stunted children - Putri, Syeptri Agiani; Novayelinda, Riri; Indriati, Ganis; Zukhra, Ririn Muthia; Amir, Yufitriana; Tampubolon, Nurhannifah Rizky; Delfitri, Meri (Alma Ata University Press, 2024)
Background: Stunting is a condition of growth failure in children resulting from malnutrition for a long time since the first 1000 days of life. One of the factors causing stunting is chronic malnutrition so that children have a small height for their age. This stunting condition will have an impact on children's health, such as impaired brain development, cognitive development, growth faltering, and low immune system. Stunting treatment is carried out starting from the first 1000 days of a child’s life until the child is 6 years old. Providing complementary food is also one of the specific nutritional interventions in the program to accelerate stunting management. Complementary food has an important role in improving the quality of health in order to optimize children's growth and development from the age of 6 months. Objectives: This research aims to explore mothers experience in providing complementary food to stunted children.Methods: This research uses a qualitative method with a descriptive phenomenological design. Participants were selected using purposive sampling techniques, resulting in 6 participants. The research data was analyzed thematically using the Colaizzi method. Results: This research found themes, namely: 1) The mother's feelings when the child was first discovered to be stunted, 2) The causes of stunting, 3) The age at which the child was discovered to be stunted, 4) History of complementary food, 5) Handling of stunting, 6) Support in caring for the child with stunting. Conclusions: Knowledge about mothers' experiences in providing MP-ASI to stunted children will help to determine appropriate interventions to improve the quality of life for stunted children. Education about giving complementary food to children with stunting conditions must be optimized to reduce the incidence of stunting in children in Indonesia, especially in Riau.